PELATIHAN PENINGKATAN KUALITAS PELAKSANAAN SISTEM AKUNTANSI INSTANSI - Handayati, Sri; Sudjana, Djudju (JIV-Jurnal Ilmiah Visi, 2010)
The research, conducted from December 2009 through January 2010, aims at evaluating the training model for staff of Education Offices in Riau Islands Province to improve the implementation quality of institution accountancy system (IAS). The method used in this research was survey covering 45 staff members of Education Offices. Data were collected by questionnaire and interview and analyzed quantitatively and qualitatively. Data analysis concludes that the existing training model suffers from weakness in its system, management, and evaluation. Further, it is recommended an alternative training model to be developed on the basis of staff’s need in improving knowledge, skills, and attitude on the SAI implementation.